(untitled) (International Journal of Engineering and Computer Science, 2017)
In this work, floating-gate MOSFET (FGMOS) based low-voltage, low-power (LV/LP) variant of voltage differencing buffered amplifier (VDBA). The linearity of the Operational Transconductance Amplifier (OTA) stage of the proposed active element is observed to increase compared to the conventional CMOS VDBA. This has been demonstrated for several supply voltages. The proposed circuit operates at low supply voltage of ±1.35V with total power consumption of 0.745mW. The application of the proposed circuit is verified through robust resistorless voltage mode universal biquad filters which are observed to implement standard filter functions. The simulations are performed through SPICE in TSMC 0.18µm technology. The work is intended to find applications in low-voltage, low-power battery-operated medical devices and other analog signal processing circuits.